(untitled) (International Journal of Communication Systems and Network Technologies, 2020)
In this situation of pandemic, where the whole country and globe is drastically affected by COVID- 19 the public sector and governments are continuously exploring new technologies to serve the different purposes to serve the citizens and the economy. Blockchain technology has gained attention across the globe of government as an emerging effective technology. Many government entities have taken steps to implement Blockchain technology. Blockchain has emerged as effective technology promising to emerge as a promising technology. The paper synthesizes literature related to application of Blockchain in different fields in the time of COVID-19. The analysis shows great potential for implementation of Blockchain to enable smart services. The study is about the application of Blockchain in different sectors such as: Contact Tracing, supply chain management, Insurance and disaster relief and weather. The study also focuses on the major issue faced by the clinicians, scientists and researchers studying data behind the crisis is that no such platform or source exits that have verified data which can be further used for study and analysis. Discussion and analysis of MiPasa for the seriousness of the ongoing situation and further what more can happen in future due to COVID-19. MiPasa is using data analytics and privacy tools; the objective is to collect data from different parts and levels.